2015
DOI: 10.1371/journal.pone.0133259
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Study on the Antioxidation Mechanism of Piceatannol and Isorhapontigenin toward Hydroxyl and Hydroperoxyl Radicals

Abstract: A systematic study of the antioxidation mechanisms behind hydroxyl (•OH) and hydroperoxyl (•OOH) radical scavenging activity of piceatannol (PIC) and isorhapontigenin (ISO) was carried out using density functional theory (DFT) method. Two reaction mechanisms, abstraction (ABS) and radical adduct formation (RAF), were discussed. A total of 24 reaction pathways of scavenging •OH and •OOH with PIC and ISO were investigated in the gas phase and solution. The thermodynamic and kinetic properties of all pathways wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…While among the conformers of isorhapontigenin, ISO and ISO-I have relative lower and similar energies. According to the bond dissociation energy (BDE) obtained by Lu etc., PIC and ISO have lower BDE values and thus have higher reactivity than PIC-I and ISO-I, respectively [32]. Therefore, in this work, PIC and ISO were chosen out from their conformers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While among the conformers of isorhapontigenin, ISO and ISO-I have relative lower and similar energies. According to the bond dissociation energy (BDE) obtained by Lu etc., PIC and ISO have lower BDE values and thus have higher reactivity than PIC-I and ISO-I, respectively [32]. Therefore, in this work, PIC and ISO were chosen out from their conformers.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study, the radical scavenging activity of PIC and ISO toward ·OH and ·OOH were theoretically investigated using the same method of M05-2X/6-311++G(d,p), and the reaction energy barriers with ZPE corrections for HAT and RAF mechanisms were also obtained [32]. We gathered Δ G ≠ sol values of the major channels in water solution of PIC and ISO scavenging ·OH, ·OOH, NO and NO 2 in Table 5, in order to research the features of PIC and ISO scavenging radicals in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural stilbenes are also good antioxidants 5 and thus the radical scavenging activity of this class of compounds is an active area of research. [6][7][8][9][10][11][12][13][14][15][16] As one of the antioxidant polyphenols found in red wine, resveratrol and its derivatives gained much attention. 6,8,9,11,12,15,17,18 Several studies demonstrated that the radical scavenging abilities of resveratrol and its metabolite piceatannol are higher than that of Trolox, the universally accepted benchmark.…”
Section: Introductionmentioning
confidence: 99%
“…Isorhapontigenin (ISO), a natural compound extracted from Chinese herb Belamacanda Chinensis , Gnetum Cleistostachyum , and grapes, is a resveratrol analogue which is widespread in plants and belongs to the group of naturally occurring polyhydroxy stilbenes (Lu, Wang, Shi, Zhang, & Li, ; Wang, Lin, & Liu, ). It has been reported that ISO plays an important role in anti‐oxidative and anti‐inflammatory (Kawakami et al, ; Xu et al, ), and it has also been revealed that ISO exhibits anti‐proliferation effect in multiple human cancers (Fang et al, , ; Siddiqui, Ahad, & Ahsan, ).…”
Section: Introductionmentioning
confidence: 99%